Upscaling and Evaluation of BARI Inclined Plate Planter (The Agriculturists, 2016)
The BARI inclined plate planter was developed for one pass tillage and seeding operation. But the planter was not capable of planting small seeds as seeds were entering between the plate and base. So, six additional MS base plates were incorporated in the planter. Three plates were redesigned and fabricated for maize seed (9 cells); for wheat, mungbean, lentil, jute, etc (32 cells) and for rice seed (11 cells). Changing of inclination of the plate is needed to use same (32 seed cell) plates for different crops and to calibrate the planter for 10% more or less seed than the predefined rates. Field test of BARI developed inclined plate planter was conducted in Gazipur, Pabna, and Barisal and its performance were evaluated. The planter was tested for sowing maize, wheat and mungbean during 2011-12. Effective field capacity and field efficiency were 0.17 ha/h and 75%, respectively. Coefficient of seed distribution uniformity and coefficient of planting depth uniformity were 97 and 94%, respectively. Time and cost saving to complete land preparation and planting of maize by inclined plate planter were 90 and 86%, respectively than conventional hand planting. The payback period of the BARI planter is 1.20 year. Break-even use time is 97 hours.The Agriculturists 2015; 13(2) 01-08